Pride & passion the Italians in America - Amoruso, Marino; Lo Bianco, Tony.; MyMar Entertainment (Firm); North Shore Entertainment (Firm) ([Bohemia, NY] : NSE Films, Inc., 2008)
A captivating and enthralling film honoring the monumental and historic accomplishments of Italian-Americans in all fields of endeavor, including entertainment, sports, business, science, politics and so much more. Special guests: Tom Lasorda, Robert Loggia, Geraldine Ferraro, Jeno Paulucci, Gay Talese, Jack Scalia, Angelo Dundee, Pat Cooper, Joe Paterno, Bernadette Castro.
Title from disc surface.
Narrated by Tony Lo Bianco.
Videodisc release of the documentary that originally aired on PBS.
DVD.
Keywords: Italian Americans -- History; Italians -- America -- History